2014
DOI: 10.1159/000357185
|View full text |Cite
|
Sign up to set email alerts
|

How Good Is the Neosquamous Epithelium?

Abstract: Background/Aims: Endoscopic radiofrequency ablation of dysplastic Barrett's esophagus (BE) combined with proton pump inhibitor therapy is commonly utilized for preventing progression of dysplastic BE to esophageal adenocarcinoma. Fundamental to the success of this and all ablative approaches is the healing of the ablated areas of BE with a stratified squamous epithelium referred to as ‘neosquamous epithelium' (NSE). Although NSE appears ‘normal' endoscopically, the reemergence of BE over time in the previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Dye-and molecule-based transfer measurements may also be made to assess the ability of molecules, such as fluorescein, to traverse the barrier as a measure of transmembrane flux. 40,41 This technique, however, is technically challenging with several technical minutiae to be considered for a successful study.…”
Section: Assessing the Epithelial Barrier Functionmentioning
confidence: 99%
“…Dye-and molecule-based transfer measurements may also be made to assess the ability of molecules, such as fluorescein, to traverse the barrier as a measure of transmembrane flux. 40,41 This technique, however, is technically challenging with several technical minutiae to be considered for a successful study.…”
Section: Assessing the Epithelial Barrier Functionmentioning
confidence: 99%
“…Although it is not covered in detail in this review of genetics and genomics in BE and EA, it is worth mentioning that recent research by a number of investigators has shown BE intestinal metaplasia has a number of properties that appear to be selective protective adaptations to the harsh, genotoxic environment in which BE arises 2, 132 . Some of these adaptations, such as crypt architecture have long been thought to have evolved as a mechanism to prevent cancer by decreasing clonal expansions of mutations 133 .…”
Section: Genomic Evolution Of Ea and Bementioning
confidence: 99%
“…Actually, fewer DNA content abnormalities and lower crypt proliferation rates have been observed in buried metaplasia than in the surface metaplastic epithelium [17]. However, according to Orlando, the neosquamous epithelium has a defective barrier function that is more permeable and leaky than normal squamous esophageal epithelium [18]. Besides the question of “risk” is the question of “origin”.…”
Section: Discussionmentioning
confidence: 99%